Influence of Copper Slag on Early Age Properties of Cement - KUMAR N V, SHASHI; ANANTHAYYA M B, Dr.; GANGADHARAPPA B M, Dr. (International Journal of Engineering and Technology, 2018)
The influence of Copper slag on early-age properties of ordinary Portland cement (OPC) has been investigated using various experimental methods. Several properties were tested by preliminary tests such as Normal consistency, Setting Time, Finess, Specific Gravity, Chemical Composition, and Compression Strength. Energy Dispersive X-ray Analysis (EDAX), X-ray diffraction (XRD), Scanning Electron Microscopy (SEM) tests are conducted to know material composition and bonding. All the Testes are carried for OPC, Copper Slag and OPC Mixed with Various Percentages of Copper Slag (CS) Viz. 5%, 10%, 20%, 25%, 30%, 35% & 40% by weight of cement. Experimental Results showed that Compression Strength Increased to Maximum extent of 5.37% at 25% replacement level copper slag. Preliminary test results shows decrease in consistency, setting time and increase in fineness, specific gravity but all the results were found to be in permissible limits at 25% replacement level of copper slag. From Chemical Composition and XRD Results it is observed that the Major compound Present in OPC is Calcium Oxide, in Copper Slag is Silicon Dioxide and for composite material (i.e. at 25% replacement level of Copper Slag) Calcium Oxide and Silicon Dioxide are responsible for Compression strength increase. The SEM image at 25% replacement level of Copper Slag with OPC shows thicker fibers which is responsible for increase in Compression strength.Â Â